Breaking the News: Max Jacob’s Le Cornet à dés (1917) - Shinabargar, Scott (Dalhousie French Studies)

(untitled) (Department of French, Dalhousie University, 2021)
The recurring pastiches of journalistic writing in Max Jacob’s seminal collection are more complex than they initially appear—critical, not merely of this discourse’s supposed objectivity, but of the assumption that the transmission of valid, valuable news is ever really sought in the first place. The indiscretions of sensationalist, and even fallacious news items appear far less surprising when we acknowledge, along with Jacob, that the esthetic pleasure orienting poetic expression – which is dependent, precisely, on a certain distortion of truthful communication – is what the public expects from its news sources as well, if unconsciously. By identifying the texts in this collection that reference topics and discursive tropes of Belle Époque journalism (and its often indistinguishable sibling, le roman feuilleton), we find that the poet simultaneously draws on the “attractive force” of such writing, drawing his reader into its intrigue, while continually disrupting any stable referential function, through linguistic play. While Jacob is hardly an engaged artist, by laying bare the ultimately unsatisfying quick fix of headline news, reconstituting the latter as an objet d’art, he reminds us of an important truth after all: the most rewarding esthetic experiences are at once more transparent – fiction acknowledged as such – and more resistant to understanding.